Implementasi Prinsip Good Governance dalam Penanganan Kasus Kriminal di Polres Sidenreng Rappang - Aan Hikma Putra; Muliani Samiri; Andi Nilwana (LPPM Universitas Abdurrab, 2026)
This study aims to evaluate the implementation of Good Governance principles in handling criminal cases at the Sidenreng Rappang Police Resort, with a focus on accountability, transparency, and community participation. Motivated by the increasing complexity of crime in the region and findings from previous studies indicating persistent weaknesses in law enforcement, this study argues that police effectiveness is determined not only by the technical competence of officers but also by the quality of governance practices in place. Employing a descriptive qualitative approach, data were collected through in-depth interviews, limited observations, and document analysis to capture actual practices in the field. The findings indicate that officers’ accountability has been pursued through procedural compliance and oversight mechanisms; however, it continues to face challenges in the form of limited access to information and perceptions of discrimination. Transparency has been implemented through information dissemination and the use of communication media, yet its application remains selective. Community participation makes a tangible contribution to supporting the investigation process, although it is constrained by obstacles such as fear of reporting and limited legal awareness. These findings underscore the need to strengthen public communication, enhance whistleblower protection, and develop community policing approaches to improve the quality of police governance at the local level.